Association between heavy metals exposure and persistent infections: the mediating role of immune function - Zhang, Huiling; Wang, Juan; Zhang, Kunlun; Shi, Jianyang; Gao, Yameng; Zheng, Jingying; He, Jingtong; Zhang, Jing; Song, Yang; Zhang, Ruifei; Shi, Xuening; Jin, Lina; et al. (Frontiers in Public Health, 2024)
Persistent infections caused by certain viruses and parasites have been associated with multiple diseases and substantial mortality. Heavy metals are ubiquitous environmental pollutants with immunosuppressive properties. This study aimed to determine whether heavy metals exposure suppress the immune system, thereby increasing the susceptibility to persistent infections. Using data from NHANES 1999–2016, we explored the associations between heavy metals exposure and persistent infections: Cytomegalovirus (CMV), Epstein–Barr Virus (EBV), Hepatitis C Virus (HCV), Herpes Simplex Virus Type–1 (HSV–1), Toxoplasma gondii (T. gondii), and Toxocara canis and Toxocara cati (Toxocara spp.) by performing logistic regression, weighted quantile sum (WQS) and Bayesian kernel machine regression (BKMR) models. Mediation analysis was used to determine the mediating role of host immune function in these associations. Logistic regression analysis revealed positive associations between multiple heavy metals and the increased risk of persistent infections. In WQS models, the heavy metals mixture was associated with increased risks of several persistent infections: CMV (OR: 1.58; 95 % CI: 1.17, 2.14), HCV (OR: 2.94; 95 % CI: 1.68, 5.16), HSV–1 (OR: 1.25; 95 % CI: 1.11, 1.42), T. gondii (OR: 1.97; 95 % CI: 1.41, 2.76), and Toxocara spp. (OR: 1.76; 95 % CI: 1.16, 2.66). BKMR models further confirmed the combined effects of heavy metals mixture and also identified the individual effect of arsenic, cadmium, and lead. On mediation analysis, the systemic immune inflammation index, which reflects the host’s immune status, mediated 12.14% of the association of mixed heavy metals exposure with HSV–1 infection. The findings of this study revealed that heavy metals exposure may increase susceptibility to persistent infections, with the host's immune status potentially mediating this relationship. Reducing exposure to heavy metals may have preventive implications for persistent infections, and further prospective studies are needed to confirm these findings.